Patterns of structural complexity and human disturbance of riparian vegetation in agricultural landscapes of a Mediterranean area - Corbacho, Casimiro; Sánchez, Juan Manuel; Costillo, Emilio (Agriculture, Ecosystems & Environment, 2003)
Riparian corridors are valuable high diversity habitats in Mediterranean-type environments and mainly in agricultural landscapes. Following a ‘vegetation complexes’ approach along ﬂuvial landscapes, the factors affecting structural complexity and human disturbance through agricultural areas in south-west (SW) Spain were analysed. Using principal component analysis and a stepwise multiple regression analysis three main results were obtained: (1) a successional vegetative gradient was noted from upper (pioneer herbaceous communities) to lower reaches of streams (closed-canopy forests) with a concomitant increase in both woody cover and habitat diversity; (2) land-use intensity associated with each of the agricultural production methods, which was mainly related to topographic irregularity, appeared to be the main cause of human disturbance in riparian areas. Thus, the closed-canopy forests located in ﬂat landscapes of lower streams were removed, highly modiﬁed or extensively fragmented; in contrast, riparian complexes placed on wild and rough landscapes of upper streams appeared as undisturbed or near-natural; (3) nearly 50% of the natural riparian vegetation of the study area has been highly modiﬁed or has disappeared, in most cases replaced by non-natural formations which have today become dominant. The protection of the few existing well-preserved riparian corridors and the restoration of highly altered riparian areas in the lower reaches of streams has become a priority in maintaining biodiversity in these agricultural Mediterranean landscapes. The extensive and cost-effective method developed for this study would be easily applicable to other large areas to evaluate the effect of human disturbance on riparian corridors
Keywords: agricultural landscapes; conservation; Human disturbance; Mediterranean areas; Riparian vegetation; Successional vegetative gradient; SW Spain

Patch occupancy by stone martens Martes foina in fragmented landscapes of central Spain: the role of fragment size, isolation and habitat structure - Virgós, Emilio; García, Francisco J. (Acta Oecologica, 2002)
We studied the response to forest fragmentation of a generalist carnivore, the stone marten Martes foina, in highly fragmented landscapes of central Spain. Five different areas (n = 178 fragments) in central Spain were surveyed. This paper analyses the relationship between fragment use by martens (measured through scat presence) and a series of variables related to the size, isolation and vegetation structure of each fragment by means of stepwise logistic regression. Size and isolation have an important effect on stone marten presence in fragments. Our results were similar to those found for other marten species in landscapes with coarse-grain fragmentation, but they contrast with other studies conducted in landscapes with ﬁne-grain fragmentation. These data suggested that in highly fragmented landscapes, size and isolation factors resulting from forest fragmentation were responsible for determining marten responses, irrespective of their habitat generalism. Management policies for the stone marten in highly fragmented scenarios require the maintenance of large forests near continuous forest tracts in mountains or riparian woodlands
Keywords: agricultural landscapes; Forest fragmentation; iberian peninsula; martes foina; size-isolation effects